The EU Industrial Strategy: Towards a Post-Growth Agenda? - Andrea Renda (Intereconomics)
Abstract Along with the Green Deal, the von der Leyen Commission immediately started to look at how to adopt an industrial strategy that would promote EU competitiveness and support the Commission’s self-assigned “geopolitical” role by boosting strategic autonomy.